Protective effects of small RNAs encapsulated in Artemisia Capillaris-derived exosomes against non-alcoholic fatty liver disease - Xu, Min; Ma, Longjun; Liang, Hongwei; Tang, Wei; Gu, Shouyong (Frontiers in Pharmacology, 2025)
IntroductionArtemisia capillaris, a traditional medicinal plant, is renowned for its therapeutic properties, including the promotion of anti-inflammatory and bile secretion. Notably, it has demonstrated efficacy in the treatment of jaundice. This study aimed to evaluate the potential of Artemisia capillaris-derived exosomes (ACDEs) as a novel therapeutic approach in non-alcoholic fatty liver disease (NAFLD).MethodsThe physicochemical properties of ACDEs were isolated and characterized using differential centrifugation, and the therapeutic efficacy was evaluated in an in vivo methionine-choline-deficient (MCD) diet induced NAFLD mouse model. In vitro, mouse hepatocytes were treated with palmitic acid (PA) to simulate a high fat environment. Intracellular triglycerides (TG) and total cholesterol (TC) levels were quantified, and Oil Red O staining was assessed. Additionally, the expression levels of proteins and RNAs associated with lipogenesis and inflammation were analyzed.ResultsThe NAFLD mouse model exhibited notable liver damage, including lipid deposition and inflammatory responses. However, treatment with ACDEs exhibited broad pharmacological activities, effectively reversing hepatic lipid accumulation and inflammatory damage. In vitro experiments revealed that ACDEs were internalized by AML12 cells via macropinocytosis and caveolin-mediated endocytosis. This treatment ameliorated dysregulated lipid metabolism and inhibited inflammatory responses. High throughput sequencing further identified a distinct small RNA profile in ACDEs, indicating the potential involvement in interspecies physiological regulation.DiscussionIn conclusion, this study provides evidence for the therapeutic potential of ACDEs in NAFLD and offers a novel perspective for the development of Artemisia capillaris-based therapies for NAFLD, related metabolic disorders, and hepatitis.